2003
DOI: 10.1055/s-0037-1613578
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the clinical significance of serum matrix metalloproteinases MMP-2 and MMP-9 in patients with various chronic liver diseases and hepatocellular carcinoma

Abstract: SummaryMatrix metalloproteinases (MMPs) have the ability to degrade basement membranes and may thus play an important role in extracellular matrix turnover in liver fibrosis and carcinogene-sis. Serum levels of MMPs have been suggested as diagnostic markers in these processes.We measured serum MMP-2 and MMP-9 by ELISA in 91 patients with chronic liver disease, including 25 patients with hepatocellular carcinoma (HCC), and in 60 controls.MMP-2 was significantly higher in patients with chronic liver disease comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 23 publications
6
29
0
1
Order By: Relevance
“…These data are going in agreement with Kuyvenhoven et al, (2003) (22) who found a significant correlation between MMP-2 and liver function (bilirubin, albumin, SGPT and prothrombin time) concluding that serum MMP-2 correlates with the severity of liver disease and may reflect changes in extracellular matrix remodeling.…”
Section: Discussionsupporting
confidence: 90%
“…These data are going in agreement with Kuyvenhoven et al, (2003) (22) who found a significant correlation between MMP-2 and liver function (bilirubin, albumin, SGPT and prothrombin time) concluding that serum MMP-2 correlates with the severity of liver disease and may reflect changes in extracellular matrix remodeling.…”
Section: Discussionsupporting
confidence: 90%
“…Obviously, due to the donor-recipient differences, the frequency of a mismatch in MMP-2 was significantly higher than in MMP-9 (57.8% versus 33.9 %, Table 2). Serum levels of MMP-2 are increased in patients with chronic liver disease and therefore a drop of MMP-2 levels was expected after OLT [11]. This decrease indeed was seen, as shown in Fig.…”
Section: The Role Of Mmp Polymorphisms In Liver Transplantationsupporting
confidence: 53%
“…Increased mRNA expression of MMP-2 was reported in liver biopsy samples of patients with cirrhosis [10]. In addition, serum levels of MMP-2 are found to be increased in patients with chronic liver disease and to correlate with the severity of the liver function impairment [11]. MMP-9 is released predominantly from neutrophils and macrophages, but the principal source in the liver is thought to be the Kupffer cell, the resident macrophage of the liver [12].…”
Section: Introductionmentioning
confidence: 99%
“…30,32,35 In brief, a polyclonal anti-MMP-2 antibody or monoclonal anti-MMP-9 antibody was used as catching antibody and appropriately diluted samples were incubated overnight at 4°C. Immunodetection of MMP-2 was performed using polyclonal anti-MMP-2 followed by biotin-labeled goat antirabbit-IgG and of MMP-9 with biotin-labeled polyclonal anti-MMP-9 antibody.…”
Section: Determination Of Mmps By Elisamentioning
confidence: 99%